Management of Ectopic Pregnancy: Comparison of Systemic Methotrexate Administration and Surgical Treatment; A Retrospective Study - Ali Cenk Özay; Özlen Emekçi; Recep Emre Okyay; Ali Rıza Taylan Bodur (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: The key to preventing maternal death is early diagnosis and effective treatment of obstetric complications. Ectopic pregnancy continues to be the number one cause of maternal deaths in the first trimester of pregnancy. Since ectopic pregnancy is the leading cause of pregnancy related death in the first trimester and accounts for 9% of all pregnancy-related deaths, the diagnosis and treatment stages should be fast and planned. In this study, our aim is to compare the results of medical treatment and surgical treatment in ectopic pregnancies. STUDY DESIGN: A retrospective case note review was undertaken of all women who presented to Dokuz Eylul University Hospital (approximately 1800 deliveries/ year) with an ultrasonographically diagnosed ectopic pregnancy from 1st January 2008 to1st March 2012. All patients' medical data were recorded. RESULTS: A total of 199 patients diagnosed with ectopic pregnancy were recruited for the study. We had total of 199 patients diagnosed with ectopic pregnancy. 90 patients were given methotrexate (MTX) treatment. From 90 (45.3%) patients who were given MTX, 29 (14.6%) of the patients had urgent surgical treatment. Second dose MTX treatment was given to 14 patients. Second dose treatment was successful in 6 patients and 8 patients had surgery. 121(60.8%) patients underwent laparoscopic salpingotomy 15 (7.5%) patients underwent laparoscopic salpingostomy and 2 (1%) patients underwent diagnostic laparoscopy. CONCLUSION: The key to preventing maternal death is early diagnosis and effective treatment of obstetric complications. Ectopic pregnancy continues to be the number one cause of maternal deaths in the first trimester of pregnancy